1989
DOI: 10.1177/153100358900200205
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Cardiac Risk in Vascular Surgical Patients: Current Status

Abstract: The prevalence of coronary arterial disease in vascular patients is now well appreciated. Several vascular surgical series from the 1960s indicated problems with both perioperative myocardial infarction (MI) and late cardiac death. 1,2 At the Cleveland Clinic from 1969 through 1978 MI accounted for 50% to 60% of operative deaths following aortic surgery 3 In addition, several longitudinal studies of patients with vascular disease have documented a high percentage of late deaths resulting from cardiac causes.4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

1991
1991
2009
2009

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 25 publications
(27 reference statements)
0
4
0
Order By: Relevance
“…The role of CABG in improving overall survival for elderly vascular patients with multiple risk factors, however, remains controversial. 1,6,[23][24][25] Elderly patients undergoing vascular surgery with elevated serum creatinine levels and left ventricular dysfunction have a reported mortality rate with CABG that exceeds 25%. 26 Certainly the 40% perioperative mortality rate associated with subsequent CABG in patients with nonfatal PMI clearly did not favorably influence their overall survival rates.…”
Section: Discussionmentioning
confidence: 99%
“…The role of CABG in improving overall survival for elderly vascular patients with multiple risk factors, however, remains controversial. 1,6,[23][24][25] Elderly patients undergoing vascular surgery with elevated serum creatinine levels and left ventricular dysfunction have a reported mortality rate with CABG that exceeds 25%. 26 Certainly the 40% perioperative mortality rate associated with subsequent CABG in patients with nonfatal PMI clearly did not favorably influence their overall survival rates.…”
Section: Discussionmentioning
confidence: 99%
“…Berens et al l reported that stroke was seen by rate of 10.9% in >65 years old patients with >80% carotid arterial stenosis [ 10 ]. The frequency of perioperative myocardial enfarction in patients underwent isolated CEA has been determined in range of 1.5% to 5% [ 11 ]. CEA is recommended in patients with symptomatic carotid disease undergoing CABG due to coronary artery disease, but it is not well determined which procedure including staged or combined CEA plus CABG should be performed in current literature.…”
Section: Introductionmentioning
confidence: 99%
“…11 Coronary artery disease is the most prominent risk factor, accounting for up to 60% of periop-erative deaths. 7,8,[12][13][14] This proportionately high cardiac morbidity can be explained by several factors. Angiographic studies have shown that 60% of patients with AAA have severe coronary artery disease.…”
mentioning
confidence: 99%